2013
DOI: 10.1124/dmd.113.051706
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Human Metabolism of Degarelix, a Gonadotropin-Releasing Hormone Receptor Blocker

Abstract: Degarelix is a decapeptide that shows high affinity/selectivity to human gonadotropin-releasing hormone receptors and has been approved for the treatment of advanced prostate cancer in the United States, European Union, and Japan. To investigate the metabolism of degarelix in humans, in vitro metabolism was addressed in liver tissue and in vivo metabolism was studied in plasma and excreta samples collected in clinical studies. In addition, drug transporter interaction potential of degarelix with selected efflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Cetrotide®, a decapeptide containing five unnatural amino acid residues approved by the FDA in 2000, was hydrolyzed by peptidase between Ser-4 and Tyr-5 and became a tetrapeptide before renal elimination ( Chia, 2021 ). Firmagon®, a decapeptide, was degraded in the liver and excreted mainly as tetrapeptide and pentapeptide fragments from the urine ( Sonesson and Rasmussen, 2013 ). Firazyr®, a decapeptide, was metabolized into two inactive fragments through the action of plasma and liver peptidase and excreted by the kidney ( Bork et al, 2007 ; Leach et al, 2015 ).…”
Section: Metabolism Stabilitymentioning
confidence: 99%
“…Cetrotide®, a decapeptide containing five unnatural amino acid residues approved by the FDA in 2000, was hydrolyzed by peptidase between Ser-4 and Tyr-5 and became a tetrapeptide before renal elimination ( Chia, 2021 ). Firmagon®, a decapeptide, was degraded in the liver and excreted mainly as tetrapeptide and pentapeptide fragments from the urine ( Sonesson and Rasmussen, 2013 ). Firazyr®, a decapeptide, was metabolized into two inactive fragments through the action of plasma and liver peptidase and excreted by the kidney ( Bork et al, 2007 ; Leach et al, 2015 ).…”
Section: Metabolism Stabilitymentioning
confidence: 99%
“…Most probably, the previous studies of Degarelix degradation considered both the drug and its hydantoin metabolite as a single active substance, due to an inappropriate analytical method used. Indeed, the sum of these two compounds is close to the initial concentration of the drug when taking into account the formation of other metabolites, such as FE 200486(1–9)‐OH, which were not studied in this work 29 . The study of the degradation of the corresponding hydantoin containing peptide did not show a reverse formation of degarelix in serum.…”
Section: Discussionmentioning
confidence: 74%
“…Degarelix has emerged as a promising GnRH antagonist for prostate cancer treatment and its pharmacologic properties and metabolic pathways have been extensively studied during the past decade. The previous studies of degarelix metabolism in humans showed that the peptide is excreted unchanged via renal pathway, but it is sequentially degraded by the hepatobiliary system 29 . Among the metabolites after 72 h mainly C‐terminally truncated nonapeptide FE200486 (1–9)‐OH was detected in plasma in the amount up to 6.3% 29 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Prescribing information at this time states it does not require dose adjustment in those with mild renal impairment but should be use with caution in those with moderate or severe impairment. [32] The same is true for those with hepatic impairment; those with mild or moderate impairment do not require dose adjustment, whereas caution should be take for those with severe hepatic impairment. There is no adjustment for age or weight and drug interactions are unlikely with degarelix as it is a poor substrate of the CYP450 system.…”
Section: Pharmacokinetics and Metabolismmentioning
confidence: 99%